Surface saline lakes in the Mediterranean Sea - E. Terzić; C. Gardiol; I. Vilibić; I. Vilibić (Ocean Science)
In the Levantine basin, it has long been known that salinity can reach a maximum in a thin layer near the surface, particularly during the warm season when summer heating, evaporation, and low mixing prevail. This water mass has been linked to the generation of Levantine intermediate and deep waters, depending on winter heat loss and wind-induced mixing. However, a recent study demonstrated that similar conditions, referred to as surface saline lakes (SSLs), can occur as far north as the Adriatic Sea. To investigate this, we analysed data from Argo profiling floats across all of the Mediterranean basins, focusing on the upper layers (up to 200 m in depth), where such lakes are known to form. We developed an objective algorithm to detect SSLs within profiles, defining a SSL according to a threshold-exceeding salinity gradient at its base. This definition allowed us to estimate SSL depth, SSL temperature and potential density (PDA) gradients at the base, as well as the Schmidt stability index which quantifies the energy needed to mix a SSL. We also ensured the quasi-continuity of Argo profiles throughout the year in our analyses, as SSLs are highly seasonal phenomena. SSLs exhibit minimum or vanishing occurrences between February and April and peak between August and October. SSLs were detected in all of the Mediterranean basins, with the highest prevalence – 65 %–70 % of the profiles between July and December – occurring in the Levantine basin. During the August–October peak, SSLs exceeded 35 % of the monthly profiles in each basin, even in the western Mediterranean, albeit with lower overall salinity levels and variable SSL ranges. These findings underscore the role of the atmospheric heat and water exchange in all of the Mediterranean basins, influencing intermediate and deeper thermohaline properties through wintertime mixing. Despite pronounced interannual and seasonal variability, our analysis of the data showed a significant positive trend in SSL depth, accompanied by decreasing thermohaline gradients (temperature, salinity, and PDA) at SSL bases through the investigated period. The observed changes raise questions about their drivers – whether they indicate ongoing climate-change-induced salinization and shifts in Mediterranean water mass dynamics or are merely manifestations of a multi-decadal variability.